Yalaga sheep - A microsatellite based genetic profile - ARORA, REENA; KULKARNI, V S; JAIN, ANAND; YADAV, DINESH KUMAR (The Indian Journal of Animal Sciences, 2016)
The genetic profile of Yalaga sheep of Karnataka was sketched based on genotypes at 25 microsatellite markers recommended for Indian sheep. A high level of genetic variation was discovered within the investigated breed as quantified from various genetic diversity estimates. Distinct alleles (240) were detected across the analyzed microsatellite loci. The mean number of observed alleles per microsatellite marker was 9.60 and number of effective alleles was 4.86. The average observed and expected heterozygosity values were 0.596 and 0.757, respectively. The mean polymorphism information content (PIC) value (0.725) reflected high level of genetic variability and utility of the markers used. The high FIS value (0.215) may have been generated due to heterogeneity among the flocks sampled within the population caused by Wahlund effect. The information generated may be useful in guiding conservation management programs for sheep breeds in Karnataka.